The Pleasure of the Eighteenth-Century Texts: The Conflation of Literary and Critical Discourse in the Early Novelistic Tradition - Maciulewicz, Joanna (Studia Anglica Posnaniensia, 2010)
One of the prominent characteristics of contemporary literature is its assimilation to critical discourse. The self-reflexivity in literature, which transforms literary texts into acts of criticism, is paralleled by theory's tendency to encroach on the literary domain. One of the findings of the poststructuralist literary theory is that descriptions of reading experience elude scientific language and are more aptly conveyed by metaphors. (A good example is Roland Barthes' The pleasure of the text.) The conflation of literary and critical discourse is not, however, peculiar to postmodernity only. The same phenomenon is observable in the eighteenth-century writings. It turns out that the self-reflexivity evident at the times of the proclaimed "death of the novel" is manifest also in the times of its birth. The aim of my paper is to analyse the metafictional reflection on readerly pleasure incorporated in early novelistic texts.